From Linguistic Landscapes to Teaching Resources: A Case of Some Rural Areas in the Province of Quezon - BALOG, PERSIEUS; Gonzales, Emmanuel (International Journal of Arts, Sciences and Education, 2021)
The study of linguistic landscape (LL) is a sociolinguistic approach that could be used to understand the diversity and power relations in a multilingual context. In the Philippines, there is a growing body of literature on describing the LL of certain local areas. However, the potentials of this LL as teaching resources have not yet been explored. This is one of the research goals of this study. Using Ben-Rafael et al.’s (2006) notion of top-down and bottom-up categorization of signs, Scollon and Scollon’s (2003) concept of place semiotics and Borg’s (2009) teaching cognition theory, this paper examines the LL of two rural areas in Quezon province and the underlying beliefs of teachers in the utilization of LL as teaching resources. Findings reveal that English occupies a hegemonic position in the LL of two rural areas in Quezon province. It indicates that both the government and private sectors give more value to English which poses challenges to the country’s national language. Furthermore, the interview responses of teachers reveal positive and important insights in the utilization of LL as teaching resources. Overall, the linguistic landscape reflects the need to learn English to function in some rural areas in the province of Quezon.